The viability of property transactions carried out by using blockchain technology: the future of Latvian land register learning from Sweden and Georgia use cases - Daukša, Diāna (Riga Graduate School of Law, 2020)
The right to property is one of the main fundamental human rights founded in almost every jurisdiction, and as such deserves the highest possible protection. Meanwhile blockchain technology over the last decade has evolved to promise extremely secure, immutable and transparent way of information transfer and storage. In order to ensure the most accurate, secure, transparent and efficient property title registration and transfer process, fight corruption and fraud, land misappropriation, countries around the world, including Sweden, Georgia, Honduras, India, Brazil, United Arab Emirates amongst others are exploring and considering the implementation of blockchain based land registry systems, while also orientating through the applicable legal requirements on blockchain based public registries, including data protection, contract law and electronic document circulation framework. The thesis analyses the legal framework applicable to blockchain based land registry, its complexity regarding interaction with innovative technology, benefits and pitfalls of introducing blockchain into public governance, followed by different country use cases and lessons learned therein, when attempting to implement a blockchain based land registry. The purpose of the thesis is to establish whether a blockchain based property title transfer process is a viable solution for furthering Latvian Land Register and the protection of right to property, or whether the existing mechanism is sufficient enough and can be improved without involving blockchain technology.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Commercial and company law; Property law